Through of Beach Space Design for Person with Disabilities Based on Universal Design Principles - Rachmita Maun Harahap; Imam Santosa (The Center for Disability Studies and Services Brawijaya University, 2019)
Most of existing public facilities in Indonesia, beach spaces become one of Â less accommodating places for people with disabilities. Researchers believe that the beach is a natural wealth of country that is entitled to be enjoyed by every layer of Indonesian society. Therefore, the beach space design becomes a place that needs to be developed in functional aspects in meeting the needs of people with disabilities. Researchers show that designers and architects are actors who have a role in creating human living space. In carrying out the role, must be aware that background and needs of human beings are very diverse. Researcher is also a hearing disabilities and â€œOne Spaceâ€ jury team begins an assessment for importance of universal design on beach space. The paper presented discussed the design of a beach space themed